THE IMPACT OF CELEBRITY ENDORSEMENT ON ATTITUDE TOWARD ADVERTISEMENT AND CUSTOMERS PURCHASE INTENTION (A STUDY OF THE FACE SHOP PONTIANAK) - admin, IQLIMA MASITA DEWI B12112009 (Jurnal Manajemen Update, 2016)
Celebrity endorsement has been the popular choice to reach potential customers and promote products in the market. Early study has also indicated this is seems to be the latest used technique by marketers because it can create awareness. The research focused on study celebrity endorsement, attitude toward advertisement and purchase intention. To explore knowledge in this area, The Face Shop Pontianak was selected. That is one of the most well known Korean cosmetic brands in Pontianak. All responses were collected by using questionnaire. The questionnaires were distributed in Pontianak and the respondents were asked to rate their perception. The result found that the attitude toward advertisement shows a significant impact on the purchase intention. And also the analysis show trustworthiness of endorser and attitude toward advertisement has positive and significant impact on purchase intention. Keywords: attractiveness, trustworthiness, celebrity endorsement, attitude toward advertisement, purchase intention